Subtarefas do teste Timed Up and Go e sua relação com as funções frontais em idosos com e sem comprometimento cognitivo leve: um estudo longitudinal - Melo, Laura Mumic de (2019)
Background: Studies have shown that there are changes in functional mobility in both cognitively preserved older adults and with mild cognitive impairment (MCI). However, the understanding of the performance over time of the Timed Up and Go subtasks - a test widely used in research and clinical practice - in these populations is not clear in the literature. Especially, the relationship that these changes over time may be related to the frontal cognitive domains. Objectives: a) to compare the performance of the TUG subtasks over time in older adults with medical diagnosis of MCI and cognitively preserved; b) to analyze the relationship between the frontal cognitive functions of these older adults at the beginning of the study, and the changes in TUG subtasks in 32 months in cognitively preserved and MCI individuals. Participants: At baseline (M1) 80 older adults (40 cognitively preserved and 40 with CCL) were evaluated, after 32 months (M2) 31 older adults (16 cognitively preserved and 15 with CCL) were evaluated. Methods: Subjects were divided in M1 into two groups: MCI and cognitively preserved. At M2 these individuals were contacted again. Functional mobility was evaluated in both moments, M1 and M2, through the adapted version of TUG in conjunction with Qualisys motion analysis system. The TUG was divided into five subtasks: sit-to-stand, walking forward, turn-to-walk, walking back and turn-to-sit. Frontal cognitive functions were assessed in M1 through the Frontal Assessment Battery (FAB) and the Clock Drawing Test (CDT). Results: There was a significant difference between the groups in the TUG sit-to-stand subtask. The MCI Group had a longer time to complete the subtask (p = 0.04) and the cognitively preserved group had a lower peak velocity of the trunk (p = 0.04) and range of motion (p = 0.02) in M2, when compared to M1. There were strong and very strong correlations between frontal cognitive functions and the difference in TUG subtasks, especially those in transition (sit-to-stand, turn-to-walk and turn-to-sit) in both groups. Conclusion: The task of getting up seems to change over time, both in cognitively preserved elderly and in those with MCI. In addition, there is a strong relationship between frontal cognitive functions and transition subtasks in cognitively preserved elderly with MCI.